Development of Descriptive Text Learning Materials Based on Local Wisdom for Seventh Grade Students of MTs Negeri 1 Manado - Maria Ulfa Rusli; Rustam Efendy Rasyid; Aswadi Aswadi; Yusmah Yusmah; Usman M (Universitas Muhammadiyah Enrekang, 2025)
The objective of this study is to develop descriptive text learning materials based on local wisdom for seventh grade students of MTs Negeri 1 Manado. To make the research more focused, the problem formulation is limited to three main issues: (1) what are the learning needs of descriptive texts in seventh grade at MTs Negeri 1 Manado; (2) what is the form and design of local wisdom–based learning materials in descriptive text learning; and (3) how effective is the implementation of local wisdom–based learning materials in descriptive text learning. This study employed a Research and Development (R&D) method using Sugiyono’s model, which consists of ten steps, ranging from identifying potentials and problems to mass production. The research subjects included material experts, media experts, and seventh grade students. Data collection instruments consisted of questionnaires, tests, observations, and interviews. The data were analyzed descriptively to determine the validity, practicality, and effectiveness of the product. The results of the study show that: (1) the developed learning materials meet the eligibility criteria in terms of content, language, presentation, and graphics, categorized as very feasible; (2) the local wisdom–based learning materials of North Sulawesi attracted students’ learning interest and facilitated their understanding of the structure and linguistic features of descriptive texts; and (3) the effectiveness test results revealed an improvement in students’ ability to write descriptive texts, with N-gain values falling into the medium to high categories. This study concludes that local wisdom–based learning materials are effective in improving students’ descriptive writing skills while simultaneously instilling the values of local wisdom in learners.